The Joyous Story of Toto - Richards, Laura Elizabeth Howe, 1850-1943; Garrett, Edmund H. (Edmund Henry), 1853-1929 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Joyous Story of Toto" by Laura Elizabeth Howe Richards is a children's novel written in the late 19th century. The narrative focuses on a young boy named Toto and his grandmother, who lives in a cozy cottage by the woods. The story reveals their sweet and whimsical lives as well as Toto's adventures, particularly his efforts to bring companionship to his blind grandmother. At the start of the story, we learn about Toto$1 (Bs loving relationship with his grandmother, who is blind and often feels lonely in their isolated cottage. The opening portion establishes their environment, detailing their cozy home and the grandmother's skilled knitting and baking. Toto, a spirited and curious child, is depicted as forgetful yet affectionate, leading to humorous situations, such as the mix-up with gingerbread ingredients. The chapter closes with Toto's resolution to introduce his forest friends to his grandmother to alleviate her loneliness, setting the stage for enchanting interactions between the animal characters and the loving grandmother. (This is an automatically generated summary.)s
Release date is 2011-02-14
David Edwards, Katherine Ward, and the Online Distributed Proofreading Team
Keywords: Animals -- Juvenile fiction; Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Grandmothers -- Juvenile fiction; Blindness -- Juvenile fiction